Tinjauan Yuridis Hukuman Disiplin Bagi Pegawai Negeri Sipil Yang Menerima Gratifikasi - Mukhamad Luthfan Setiaji (PSHPM Untag Semarang, 2025)
The capacity to adhere to duties and stay clear of restrictions outlined in statutory regulations is known as civil servant discipline. Accepting gifts associated with their position, such as gratuities, is prohibited for civil officers. Civil servant penalties will be imposed on civil servants who break the restrictions as stipulated in the statute. Utilising secondary data sources and qualitative analysis methodologies, the study employed the normative juridical research method. The findings demonstrated that federal servants would face disciplinary action if they accepted gifts or gratuities associated with their position. Everyone would face harsh disciplinary action, including dishonourable discharge, if it were established that you had broken the rules.